Straightforward Synthesis of Novel Acene-Based Aryne Precursors - Rodríguez-Lojo, Diego; Peña, Diego; Pérez, Dolores; Guitián, Enrique (Synlett, 2015)
Large polycyclic o-(trimethylsilyl)aryl triflates are easily obtained by reaction of commercially available bisaryne precursors with cyclopentadienones. The transformation involves controlled generation of one of the aryne functionalities, trapping by Diels–Alder reaction with a dienone, and chelotropic extrusion of CO. The newly synthesized triflates are precursors of acene-based arynes, including a didehydropentacene.
Keywords: arynes; polycyclic aromatic hydrocarbons; acenes; Diels–Alder reaction; cycloadditions